Drama, rumors & secrets : staying true to yourself in changing times - Holyoke, Nancy (Smart girl's guide, 2015)
Shares expert advice for how to avoid and diffuse drama-related challenges including jealousy, gossip, and cyberbullying, offering insights into the psychology of drama based on the experiences of real girls.